Immunemorphological aspects of different variants of generalized parodontitis. - Samoilenko, A. V.; Shpon’ka, I. S.; Babenko, L. M.; Poslavs’ka, O. V.; Shi, Unin (Морфологія / Morphologia / Morfologìâ, 2013)
This article is devoted to the study of the prognostic value of immunohistochemical markers of local immune homeostasis of parodontal with definition of CD3+, CD4+, CD8+, CD20+, CD68+, CD138+ cells of the immune series and S100 + dendritic cells, angiogenesis CD34 and VEGF, reparative proliferation Ki-67, stromal degradation MMP-1 and inducible nitric oxide synthase iNOS in inflammatory processes periodontal definition of morphological relations between the values of immunohistochemical indices and aggressiveness of generalized parodontitis.